Exploring the effect of using active learning strategies on Iranian intermediate female EFL learners reading comprehension: a mixed methods study - Majdi, Zahra; Khalili Sabet, Masoud; Mahdavi-Zafarghandi, Amir (Frontiers in Education, 2025)
This study investigates the impact of active learning strategies (ALSs) on reading comprehension, engagement, motivation, and enjoyment among intermediate Iranian EFL learners, and explores their perceptions of ALS in reading. It addresses the prevalence of passive learning methods in Iranian EFL education and aims to evaluate the potential of ALS. Eighty female high school students were divided into experimental and control groups. The experimental group participated in ten active learning sessions. Quantitative data (pre- and post-tests) assessed reading comprehension, engagement, motivation, and enjoyment. Qualitative data were gathered via semi-structured interviews to explore student perceptions. Quantitative data revealed significantly higher post-test scores in reading comprehension for the experimental group using ALSs. Qualitative data highlighted positive student perceptions, including improved reading skills, strategic approaches to texts, and enhanced comprehension due to diverse activities and supportive peer interaction. No significant differences were found in engagement, motivation, or enjoyment. The findings underscore the potential of ALS to improve EFL reading comprehension. The discrepancy in engagement, motivation, or enjoyment may be attributable to cultural factors and learning preferences within the Iranian EFL context. Challenges such as difficulties with complex texts, unfamiliar vocabulary, time constraints, and occasional issues with group dynamics were also identified. The findings emphasize the need for culturally sensitive implementation, ongoing support, and strategic adjustments. Further research is recommended on the long-term effects of ALSs on learner engagement and motivation.